Pemerintah yang Efisien, Tanggap, dan Akuntabel - Agus Dwiyanto (Magister Administrasi Publik, 1997)
Current issues which reflecting the difficulties in establishing efficient, responsive and accountable government are partly because of too much orientation on economic development while neglecting administrative and political reformation. Lack of attention to administrative and political reformation which create the so-called ‘administrative state’ has brought about bureaucratic pathology and practical collusive and corrupt behaviors. Power and authority, which concentrated within the public bureaucracy have also obstruct people political capability to control the government. This article offers cultivation of bureaucrat ethics as a strategy to create an efficient, responsive, and accountable government. Bureaucrat ethics could be a fundamental code for public bureaucrats so that they would be able to make policies which in response to public interest and people’s original values. Only if this public ethics is institutionalized then bureaucrats would have a good guidance in applying discretionary power, even when political control and regulation are no longer effective.